The Effect of Leader Expectation and Cowoker Pressure on the Research Performance of Private University Lecturers Mediated by Organizational Support - Jumantara, Gusye; Nurfahmi, Ilham; Rosnidah, Ida; Kartono, Kartono (CV. AFDIFAL MAJU BERKAH, 2024)
Purpose - Lecturer research performance is critical for university success, yet the interplay between leader expectation, coworker pressure, and organizational support remains underexplored. This study aims to investigate the effect of leader expectation and coworker pressure on lecturer performance, with organizational support as a mediating variable. A quantitative descriptive method was employed using data from 90 lecturers sampled from private universities in Cirebon City, Indonesia. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results show that leader expectation significantly impacts lecturer research performance, while organizational support mediates the relationship between coworker pressure and research performance. This study introduces a novel perspective on the positive role of coworker pressure in enhancing research performance when supported by strong organizational support. Universities should prioritize leadership development, foster collaborative work environments, and establish policies that promote research productivity through enhanced organizational support, such as accessible research facilities and effective communication channels.